METODE META-HEURISTIC UNTUK MENYELESAIKAN PERMASALAHAN PENJADWALAN PRODUKSI: CROW SEARCH ALGORITHM - Antono Adhi; Riza Radyanto (Jurnal Ilmiah Dinamika Teknik, 2018)
Scheduling is part of the production process. The scheduling process is done in preparation for the production process. In practice, rescheduling can also be done if there is a change in the production process. The scheduling process is completed for each task which is usually called work on available machine resources. This process determines which work will be done first. Every production process has a purpose. The usual goal taken is the time obtained by the total production process to a minimum or makespan. Another goal is to get late fees (delay) and too fast the work done (beginning), as small as possible. The purpose of production scheduling is so that the production process can be completed optimally, namely with the smallest time and cost. In the end, scheduling includes the NP-hard process in its completion. This process is difficult to do with the usual exact method if you have a large number of jobs. In this case the process will take a very long time. Therefore the scheduling process can only be completed by the meta-heuristic method. In this method, optimal results can be received at the time of receipt that is not too long. One of the meta-heuristic methods used in this study is to use the crow search algorithm (CSA) algorithm. This algorithm is quite simple but gives good results to complete production scheduling. Keywords: Production Scheduling, Optimal, Meta-Heuristics, Crow Search, Algorithm